Assessment of Factors Affecting the Adoption of Alternative Sources of Energy in Limbuli, Malawi - Mwakabanga, Bettie; Mzuza , Maureen Kapute (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 8, 2023)
There is an increased demand for energy due to the continuously growing human population. Due to the increase in energy demand, fossil fuel reserves are being rapidly depleted; dependence on fossil fuels as a source of energy damages the environment in many aspects. This practice can be halted if we switch to renewable energy sources like wind, solar and hydrophone. This study assessed factors that lead to low Adoption of alternative energy sources. The study took place in Limbuli in Mulanje, Malawi. It used stratified sampling to sample 80 households in the peripherals of the Limbuli estate. Fifty-seven households were interviewed to gain an in-depth understanding of factors that affect the Adoption of alternative energy sources. It found that the expensiveness and unreliability of alternative energy sources affect their Adoption. It also shows a direct relationship between adopting alternative energy sources and education and income level. Further, it indicates that culture and knowledge of alternative energy sources have less significance on their Adoption. It concludes that the Adoption of alternative sources of energy continues to be an area of further consideration. The study recommends that Lessons on alternative energy sources that focus on the mindset change towards alternative energy sources should be included in primary schools, and awareness campaigns should be done in the community.